(3QSGdI JbdjO dGMb GdJbdjO GdChd Edi GdTjN GdeNJGQs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG dGHGQ GdYdGe GdMGce HGdMb hehdi GdCfGe ef GdYHO GdebJfi HgG GdOjf hdSGf GdeDefjf hSfO GdehMOjf s
(3BNQgG (B:s
(3aGdehdi HbHhdgG jhabc ai CaYGdc hjSYOc HUGdM CYeGd Je GdJbdjO HefI hdi GdfYeI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B45s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3abg GdePGgH GdCNQis